Changes in the proverb formula in Finnish Bibles from 1642 to 1992 - Priiki Katri (De Gruyter Mouton, 2022)
The article studies a subtype of the Finnish generalizing relative clause, referred to as the proverb formula. A generalizing relative clause refers to any person who fills the described condition. The proverb formula is used frequently in the Finnish translations of the Bible in the Book of Proverbs. The study examines two aspects that vary in this structure in Finnish editions from 1642 to 1992: the head pronoun of the relative clause and the order of the relative clause and the main clause. In the oldest of the studied translations, the most frequent one variant or the proverb formula begins with the relative clause, and the relative clause head in the main clause is a personal pronoun (hän). For the order of the structure, a clear model is found in the source texts of the translation. In later editions, personal pronoun heads were eliminated. Interestingly, they are not replaced with demonstrative heads, which would follow the most frequent proverb formula structure in Finnish vernacular and would also be recommenced by grammar guides. Instead, a variant with omission of the head pronoun gains in frequency. Variations within the proverb formula increase when the order with the main clause preceding the relative clause gains in frequency. The preference for omission of the head pronouns is not easily explainable. The article proposes that this variant was a conscious stylistic choice for solemn, biblical language.